Risk management tools for safety professionals - Lyon, Bruce K.; Popov, Georgi (Engineer) (American Society of Safety Professionals, 2018)
Practical guidance on fundamental risk management and prevention through design (PtD) tools. Addresses seven of ABET's criteria for safety science programs--